Differential alteration of drug-metabolizing enzyme activities after cyclophosphamide/adriamycin administration in breast cancer patients - Elkiran, Tamer; Harputluoglu, H.; Yasar, U.; Babaoglu, M.O.; Dincel, A.K.; Altundag, K.; Bozkurf, A. (My University, 2007)
Cyclophosphamide (CPA) and adriamycin (ADR) are widely used drugs for cancer chemotherapy. It has been reported that CPA and ADR singly or in combination could alter activities of a variety of drug-metabolizing enzymes in animals via multiple mechanisms. However, the effects of CPA/ADR on drug metabolism are largely unknown in human beings. Losartan metabolism has been suggested as a marker for determination of CYP2C9 activity. Caffeine is a commonly used probe to assess the metabolic activities of CYP1A2, CYP2A6. N-acetyltransferase 2 (NAT2) and xanthine oxidase (XO). The present study was designed to analyze the effects of CPA/ADR on these drug-metabolizing enzymes by using losartan and caffeine as probe drugs. A single oral dose of 25 mg losartan and a cup of instant coffee was given to 15 breast cancer patients on three occasions (before, and 2-4 h and 3 weeks after the adjuvant CPA/ADR chemotherapy [600 mg CPA/m2/day, 60 mg ADR/m2/day]). Losartan, caffeine and their metabolites were analyzed by using high-pressure liquid chromatography. When compared with baseline, CYP1A2 activity was increased by 20% and CYP2C9 activity was decreased by 315% 3 weeks after the administration of CPA/ADR chemotherapy (p = 0.05). The chemotherapy did not change the activities of CYP2A6, NAT2 or XO. CPA/ADR treatment caused a differential effect on drug-metabolizing enzyme activities, and this may contribute to predicting the efficacy and toxicity of chemotherapeutics, as well as understanding the drug-drug interactions. © 2007 Prous Science. All rights reserved.
Keywords: Adriamycin; Cyclophosphamide; Cytochrome P450; Induction; Inhibition